(3efXheI GdUHjGf aj eUWdM GdMOjKs
(3ChdgG (B:s
(3GdMeO ddg JYGdi hcai Ke SdGeg Ydi ef GUWai hHYO aGdMOjK NjQ Yde jWdH HGdMaX hUQa GdcQje s
(3BNQgG (B:s
(3hdjS ai GdfSGA ef bO MQLJ ajeG YdefG Ch HVYa bOMJ hGdMeO ddg Ydi GdJeGe Ke UdGI Gddg HGdSdGe Ydi GdfHi GdeUWai hGdBd eG fXeJ bdGFO GdCdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdMOjK h GdeUWdMs